Gradient power modified ohmic heating curing to prepare hybrid carbon fibers/high performance concrete under deep-freeze low temperature. (2nd May 2022) - Ouyang, Mingzhe; Tian, Weichen; Liu, Yushi; Wang, Wei
Highlights: Multi-step OH curing was originally presented for on-site HPC construction at ultra-low temperature. Heat transfer theory was used to establish multi-step OH curing program to restrain thermal expansion at early age. 3SP OH cured samples exhibited comparable mechanical properties with HTS cured samples. Refined pore structure and higher ACL value were observed in 3SP OH cured samples. Abstract: The on-site fabrication of high-performance concrete (HPC) under ultra-low temperature environment is challenging the research community. This work presents a gradient power modified ohmic heating (OH) curing to stimulate the strength formation of conductive carbon fiber/carbon nanofiber reinforced high performance concrete (HCF-HPC) at ultra-low temperature. Specifically, the gradient power loading strategy with three-step power (3SP) OH curing method was experimentally and numerically designed. Heat transfer mathematical model based on the principle to suppress thermal expansion has been established to regulate the curing temperature of each curing step from around 30℃ to 70℃ for the samples subjected to OH curing with increasing curing steps. The results showed that the compressive strength of the 3SP OH cured HCF-HPC samples reaches up to 103.3 MPa, which is comparable with that of the sample cured by high-temperature steam curing (107.5 MPa). Moreover, multiscale analyses have been conducted to verify the positive effect of 3SP OH curing on pore structure, hydration products and hydration degree of HCF-HPC samples.